Systemic immunological profile of children with B-cell acute lymphoblastic leukemia: performance of cell populations and soluble mediators as serum biomarkers - Carvalho, Maria Perpétuo Socorro Sampaio; Magalhães-Gama, Fábio; Loiola, Bruna Pires; Neves, Juliana Costa Ferreira; Araújo, Nilberto Dias; Silva, Flavio Souza; Catão, Claudio Lucas Santos; Alves, Eliana Brasil; Pimentel, João Paulo Diniz; Barbosa, Maria Nazaré Saunier; Fraiji, Nelson Abrahim; Teixeira-Carvalho, Andréa; et al. (Frontiers in Oncology, 2023)
Children with B-cell acute lymphoblastic leukemia (B-ALL) have an immune imbalance that is marked by remodeling of the hematopoietic compartment, with effects on peripheral blood (PB). Although the bone marrow (BM) is the main maintenance site of malignancy, the frequency with which immune cells and molecules can be monitored is limited, thus the identification of biomarkers in PB becomes an alternative for monitoring the evolution of the disease. Here, we characterize the systemic immunological profile in children undergoing treatment for B-ALL, and evaluate the performance of cell populations, chemokines and cytokines as potential biomarkers during clinical follow-up. For this purpose, PB samples from 20 patients with B-ALL were collected on diagnosis (D0) and during induction therapy (days 8, 15 and 35). In addition, samples from 28 children were used as a control group (CG). The cellular profile (NK and NKT-cells, Treg, CD3+ T, CD4+ T and CD8+ T cells) and soluble immunological mediators (CXCL8, CCL2, CXCL9, CCL5, CXCL10, IL-6, TNF, IFN-γ, IL-17A, IL- 4, IL-10 and IL-2) were evaluated via flow cytometry immunophenotyping and cytometric bead array assay. On D0, B-ALL patients showed reduction in the frequency of cell populations, except for CD4+ T and CD8+ T cells, which together with CCL2, CXCL9, CXCL10, IL-6 and IL-10 were elevated in relation to the patients of the CG. On D8 and D15, the patients presented a transition in the immunological profile. While, on D35, they already presented an opposite profile to D0, with an increase in NKT, CD3+ T, CD4+ T and Treg cells, along with CCL5, and a decrease in the levels of CXCL9, CXCL10 and IL-10, thus demonstrating that B-ALL patients present a complex and dynamic immune network during induction therapy. Furthermore, we identified that many immunological mediators could be used to classify the therapeutic response based on currently used parameters. Finally, it is noted that the systemic immunological profile after remission induction still differs significantly when compared to the GC and that multiple immunological mediators performed well as serum biomarkers.